Back to basics: Upholding four fundamental tax principles for Indonesia’s fiscal independence - Sinaga, Suhut Tumpal (WIM Solusi Prima, 2025)
This paper revisits the four foundational principles of taxation—neutrality, simplicity, certainty, and equity—as the bedrock of a fiscally independent and socially just tax system in Indonesia. Despite commendable progress in post-pandemic fiscal consolidation, Indonesia’s tax-to-GDP ratio has stagnated near 12 percent, far below the Asia-Pacific average of 19 percent. The study combines historical review, comparative analysis, and institutional assessment to argue that reaffirming these principles is essential to attain the country’s Vision 2045 target of high-income status. Drawing on OECD, IMF, and DDTC data (2019–2025) and the most recent academic literature, the paper shows that distortionary incentives, administrative complexity, and uneven enforcement undermine revenue potential. The analysis culminates in a policy framework that aligns neutrality, simplicity, certainty, and equity with digital-era governance and sustainable fiscal independence.